2019
DOI: 10.1002/cnr2.1185
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling nanotubes: A bridge for heterogeneity in glioblastoma and a new therapeutic target?

Abstract: BackgroundThe concept of tumour heterogeneity is not novel but is fast becoming a paradigm by which to explain part of the highly recalcitrant nature of aggressive malignant tumours. Glioblastoma is a prime example of such difficult‐to‐treat, invasive, and incurable malignancies. With the advent of the post‐genomic age and increased access to next‐generation sequencing technologies, numerous publications have described the presence and extent of intratumoural and intertumoural heterogeneity present in glioblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 128 publications
0
19
0
Order By: Relevance
“…A further feature of the cellular communication via TNTs is the facility to exchange cargoes over long distances in a very direct and selective manner. In the tumor microenvironment, there is a great heterogeneity in the composition of several kinds of cells including stromal, tumor, red blood cells and so on [79, 100]. Due to this high complexity in the cellular matrix of a tumor region, non-contact cellular communication by secretion of signal molecules or contact cellular communication by gap junctions which require an immediate proximity of donor and recipient cell, are very limited and the flexible TNTs connections may present a more promising opportunity for cells to communicate and network among each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further feature of the cellular communication via TNTs is the facility to exchange cargoes over long distances in a very direct and selective manner. In the tumor microenvironment, there is a great heterogeneity in the composition of several kinds of cells including stromal, tumor, red blood cells and so on [79, 100]. Due to this high complexity in the cellular matrix of a tumor region, non-contact cellular communication by secretion of signal molecules or contact cellular communication by gap junctions which require an immediate proximity of donor and recipient cell, are very limited and the flexible TNTs connections may present a more promising opportunity for cells to communicate and network among each other.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore conclude that TNTs are a crucial target which has to be investigated in order to understand therapy outcome and to be able to find new and more effective tumor treatment. This opinion is shared by many researchers and in the last few years several reviews covering the role of TNTs in cancer as well as the paradigm to exploit intercellular communication to better treat cancer have been published [58, 79, 80, 100, 106108].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Further, Nakamura et al showed that the interactions among Sig1-Rs, cocaine, and EVs may regulate synaptic transmission in the brain through the release of 2-AG (2-arachidonoylglycerol; an endocannabinoid that is increasingly synthesized with cocaine stimulation); this release of 2-AG contributes to the inhibition of GABAergic input to dopamine neurons [113]. Interestingly, in a glioblastoma culture model, cocaine exposure not only increased EV release but also increased tunneling nanotubule (TNT) formation [114][115][116]; both EVs and TNTs are highly correlated with the development of many diseases, such as glioblastoma and neurodegenerative diseases [117,118]. Further, cocaine self-administration has been shown to reduce the internalization of neuronal exosomes, particularly in astrocytes in the nucleus accumbens (NAc); this reduction was then reversed by extinction training [119].…”
Section: Cocainementioning
confidence: 99%
“…Indeed, the question whether neuronal activity can promote glioma progression and eventually how efficient this promotion may be has been investigated for many years without a true answer being found. Nowadays, an increasing body of evidence suggests a possible role of neurons and neuronal activity in fuelling glioma growth and neoplastic cell invasion [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Satellitosis In Neurological Diseasementioning
confidence: 99%